Christological Foundations for an Ecological Ethic: Learning from Bonhoeffer - Burkholder, Benjamin J. (Scottish journal of theology, 2013)
In an age where the church needs to foster moral concern for the environment, some are suggesting that Christian theology itself must be changed to produce this result. This article argues that such emendations are unnecessary because Dietrich Bonhoeffer, working a couple of decades before ecological concern was even seen as necessary, manages to craft a theological and ethical approach which is sensitive to ecological concern while retaining large portions of the Christian tradition. Bonhoeffer's anthropology robustly affirms humanity's connection with the natural environment and does not separate humans from the natural order. In fact, his novel approach to the image of God emphasises the necessity of human physicality and the ethical responsibility for the other, which seems to be extendable to the natural order as well. In addition, Bonhoeffer's interpretation of the command to have dominion sees the injunction as a call to be ‘bound’ to nature as a servant, not as a lord free to exploit the earth for wanton pleasure. Consequently, Bonhoeffer interprets the industrial revolution as the failure of humans to rule and serve creation well. Finally, his anthropology, unlike many in the tradition, does not extradite humans from the world, but rather situates them entirely within the matrix of interlocking relationships in the natural world. While Christian soteriology has been criticised for shifting Christian concern away from the environment and life in this world, Bonhoeffer's soteriology overcomes this criticism. Bonhoeffer vociferously repudiates two kingdoms theology in favour of a single unified reality of Christ, which unites God's work of creation and redemption into a unified whole. Furthermore, he interprets the incarnation as a robust affirmation of God's creation and thereby life in this present world. Finally, Bonhoeffer posits redemption encompassing the entire world order, rather than seeing humans as its unique constituents. Bonhoeffer's ethics of responsible action shows that humans need to evaluate not just their immediate actions, but also the long-term consequences of their actions, especially when it comes to use of the environment, both for the sake of other humans and for the sake of following Christ. Since disciples of Christ are supposed to be working towards the reality of Christ, one can conclude that Bonhoeffer's thought encourages humans to work towards the harmony that is to typify creation in the eschaton. Thus, Bonhoeffer's ethics encourages a moral concern for the environment both as a means of neighbourly love and as a means of following Christ.